Стая: [роман] / Марьяна Романова - Романова Марьяна (Серия "Бестселлеры Марьяны Романовой", 2016)
Экземпляры: Ф. 13 (20200203) / Инвентарный номер: 47578 / Цена: 90.00 / Авт.знак: Р 69 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6